2016
DOI: 10.1371/journal.pone.0152515
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis Provides Insights into the Pathogenicity of Flavobacterium psychrophilum

Abstract: Flavobacterium psychrophilum is a fish pathogen in salmonid aquaculture worldwide that causes cold water disease (CWD) and rainbow trout fry syndrome (RTFS). Comparative genome analyses of 11 F. psychrophilum isolates representing temporally and geographically distant populations were used to describe the F. psychrophilum pan-genome and to examine virulence factors, prophages, CRISPR arrays, and genomic islands present in the genomes. Analysis of the genomic DNA sequences were complemented with selected phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 63 publications
2
60
0
Order By: Relevance
“…Similarly, Touchon et al reported that there were no incomplete prophage elements in F. branchiophilum FL-15 (Touchon et al, 2011 ). This may be partially explained due to the presence of multiple CRISPR loci in F. psychrophilum (1~2 loci) (Castillo et al, 2016 ), F. columnare (at least 3 loci) (Kayansamruaj et al, 2017 ), and F. branchiophilum FL-15 (at least 3 loci) (Touchon et al, 2011 ; Barrangou and Marraffini, 2014 ; van Houte et al, 2016 ). It is interesting that we did not detect any CRISPR elements in F. spartansii T16 T , which may coincide with presence of prophages, genomic islands, and conjugative transposons in its genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Touchon et al reported that there were no incomplete prophage elements in F. branchiophilum FL-15 (Touchon et al, 2011 ). This may be partially explained due to the presence of multiple CRISPR loci in F. psychrophilum (1~2 loci) (Castillo et al, 2016 ), F. columnare (at least 3 loci) (Kayansamruaj et al, 2017 ), and F. branchiophilum FL-15 (at least 3 loci) (Touchon et al, 2011 ; Barrangou and Marraffini, 2014 ; van Houte et al, 2016 ). It is interesting that we did not detect any CRISPR elements in F. spartansii T16 T , which may coincide with presence of prophages, genomic islands, and conjugative transposons in its genome.…”
Section: Discussionmentioning
confidence: 99%
“…(McBride et al, 2009 ; Barbier et al, 2012 ; Kumru et al, 2017 ) and additional genome sequence data are now available for multiple strains of the fish pathogens F. columnare (Bartelme et al, 2016 ; Zhang et al, 2016 ), F. psychrophilum (Wiens et al, 2014 ; Wu et al, 2015 ), and F. branchiophilum (Touchon et al, 2011 ). These studies have revealed some of the processes by which flavobacterial fish pathogens are believed to colonize, attack, and survive within fish hosts (Duchaud et al, 2007 ; Castillo et al, 2016 ), as well as how some of the molecular mechanisms vary amongst strains (Wiens et al, 2014 ; Wu et al, 2015 ; Bartelme et al, 2016 ; Zhang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…STs that did not form part of a CC were referred to as singletons. All isolates within the publicly accessible MLST database for F. psychrophilum (n ϭ 1,097; https://pubmlst.org/ fpsychrophilum/) (15), including all previously typed isolates from North America (n ϭ 107) (7,13,39), along with the 314 isolates of this study, were included in the eBURST v3 (37,38) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Castillo et al (2016) recently reported that F. psychrophilum harbors at least 3373 genes and a core genome minimum of 1743 genes, with putative virulence factors uniformly distributed among 11 isolates from different sources and locations (Castillo et al, 2016). Remarkably, all of these isolates show similar capacities to form biofilms, with implications for their virulence and pathogenicity.…”
Section: Introductionmentioning
confidence: 99%